Sinergisme Ekstrak Campuran Daun Mimba dan Serai terhadap Walang Sangit pada Tanaman Padi (Oryza sativa L.) - Syarief, Mochamad; ., Fitria (JURNAL AGROPLANT, 2024)
The aim of the research was to determine the synergism of a mixture of Azadirachta indica and Cymbopogon nardus extracts on L. oratorius. and its efficacy on the population, intensity of attacks and rice yields. This research began in October to November 2023 at the Plant Protection Laboratory of the Jember State Polytechnic and Rice Plants in Dukuh Mencek Village, Sukorambi District, Jember Regency. The research method is as follows: Bioassay test to determine the toxicity of LC95 against L. oratorius imago, using 6 different concentrations, namely control (distilled water), 5%, 10%, 15%, 20% and 25%. Each 10 insects were tested, repeated three times, using the feed immersion method for 10 seconds. LC95 toxicity using Probit analysis, with PoloPlus 1.0 software. Next, it is used to determine the synergism of the bioinsecticide mixture and field tests. Field tests compared the efficacy of bioinecticide on the population and intensity attacks and crop yields. The results of the research were: bioinsecticide, a mixture of neem and lemongrass leaf extracts, was more toxic than those used alone, and has a synergistic impact. The population, intensity of attacks  and yields compared to Imdakloprid were not significantly different.